Assessment of Directly Observed Therapy Short Course (DOTs) Program Therapy in Treatment of Tuberculosis in Al-Sader City 2003-2005 - Almissar, ahmed; rashid, Buthaina; Rhaman, Osama (Iraqi National Journal of Nursing Specialties, 2013)
Objectives: Assessment outcome of DOTS (Directly observed therapy short course) program in Al-Sader City Sector that was established by the WHO. Methodology: Three cohorts groups of patients attending Baghdad TB institute and TB center in Al-Sader city were followed retrospectively. The 1st cohort included (314) patients registered in year (2003), the 2nd cohort included (327) patients registered in year (2004), the 3rd cohort included (321) patients registered in year (2005). The collected data were analyzed for case detection, treatment outcomes, retreatment outcomes, treatment success, and retreatment success in regard to time, age and sex. Results: The following rates were extracted for the three cohort: Case detection rate within 1st, 2nd, and 3rd cohort were (73.36%, 64.24%, and 71.49% respectively).Treatment outcomes (cured, completed treatment, defaulters, treatment failure, died and transfer out) of new smear positive patients within the 1st, 2nd and 3rd were (71.7%, 12.7%, 10.2%, 3.5%, 1%, 1%), (64.8%, 19.9%, 0.9%, 7%, 0.6%, 6.7%) and (61.4%, 24%, 3.1%, 5.9%, 0.6%, 5% respectively).Retreatment outcomes (cured, completed treatment, defaulters, treatment failure, died and transfer out) within 1st, 2nd and 3rd cohort were (55.6%, 7.9%, 6.6%, 15.2%, 4%, 10.6%), (44.9%, 7.7%, 2.6%, 21.8%, 4.5%, 18.6%) and (41.8%, 14.6%, 11.4%, 19.6%, 1.9%, 10.8% respectively. Treatment success rate within the 1st, 2nd and 3rd cohort were (84.39%, 84.7%, and 85.35%) respectively. Retreatment success rate within the 1st, 2nd and 3rd cohort was (63.57%, 52.56%, and 56.32%) respectively. Recommendation :Increase case detection rate through increase health awareness to the community about the mode of transmission and risk of TB disease, Increase the training of health team so that they can follow up of patients at home, Increase follows up of defaulters to be able to deal with them and a study for relapses cases is recommended